2022
DOI: 10.3390/ijerph20010030
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and DGT Based Bioavailability of Cadmium in the Soil–Crop Systems from the East Edge of the Dongting Lake, China

Abstract: Contamination of heavy metals (including the cadmium, Cd) in agricultural soils has become an increased issue, posing a threat to the crop safety and human health. In order to evaluate the contamination characteristics and bioavailability of Cd in the soil–crop systems from the East edge of the Dongting Lake, four kinds of agricultural products for typical crops (rice, peanut, sweet potato, and corn) and corresponding rhizosphere soils were collected and analyzed for the Cd concentrations. The technique of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…C DGT in rhizosphere soil of several crops (rice, corn, peanut, and sweet potato) also showed good correlation with its accumulation in those crops ( r 2 in the range 0.64–0.90) (Guo et al 2023 ). In a study on paddy soil, C DGT of Cd was correlated with Cd concentration in the rice grains, straws, or roots.…”
Section: Dgt Applications For Heavy Metal Labile Fractions In Soilmentioning
confidence: 99%
“…C DGT in rhizosphere soil of several crops (rice, corn, peanut, and sweet potato) also showed good correlation with its accumulation in those crops ( r 2 in the range 0.64–0.90) (Guo et al 2023 ). In a study on paddy soil, C DGT of Cd was correlated with Cd concentration in the rice grains, straws, or roots.…”
Section: Dgt Applications For Heavy Metal Labile Fractions In Soilmentioning
confidence: 99%
“…The results revealed that frequent tire friction and brake wear significantly increased the exchangeable fraction of these toxic metal(loid)s, except for Pb (0.09 mg/kg). The chemical interaction of metal(loid)s (bearing particles) with soil/dust components, including clays, Fe/Mn (oxyhydr)oxides, organic matter, and silicate minerals, as well as their behavior with respect to the soil pH, resulted in their repartitioning [78,80,81]. The low sorption ability/capacity of trace metal(loid)s by dust often results in substantial mobility, and a low content of iron/aluminum oxides and organic matter may also favor trace metal(loid) immobilization [82].…”
Section: Sequential Extraction Of Trace Metal(loid)s From Dust and Ga...mentioning
confidence: 99%
“…Heavy metals, generally referring to metals and metalloids with a density greater than 4.5 g/cm 3 such as Cd, Cr, Hg, Pb, Cu, Zn, Ni and As, are considered as the main hazardous trace elements and pollutants that are preferentially monitored and controlled. Soil heavy metal contamination attracts great attention around the world, due to its high toxicity at low content thresholds [1,2], persistence and extreme difficulty in removal by natural degradation [3], and bioavailability [4][5][6][7]. The accumulation of heavy metals in soil can degrade soil quality, disrupt ecological services and create serious risks for human health [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%